Self-Directed Learning (SDL) In Higher Education: Practices and Issues - Abeyrathne, Dilani Kanishka; Ekanayake, Sakunthala Yatigammana; Abeyrathne, Dilani Kanishka (Asian Journal of Electrical Sciences, 2020)
SDL is considered to be a fundamental educational goal. However, higher education institutes are challenged when promoting SDL. Therefore, the present study aims to, explore existing practices of self-direct learning implemented in the Faculty and to identify problems of undergraduates when they are engaging with self-direct learning practices in the Faculty. The study reflects that most of the students are familiar with the term self-directed learning. They had experienced with self-direct learning activities of assignments, class presentations conducted by students, group work or group discussions, practical/laboratory classes, field visits/field work, quizzes, tutorial classes, independent research project, e- learning, independent learning, food processing plant, in-plant training/industrial training, viva and farmer training program. Students express different learning preferences. However, students struggle with some issues when they engage with SDL. The issues are mainly related to course curriculum, teaching process, students’ factors and lecturers’ issues.